2019
DOI: 10.1039/c9ra03050f
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite lattice oxygen contributes to low-temperature catalysis for exhaust gas cleaning

Abstract: A Pd catalyst supported on Ba-substituted LaAlO3 perovskite (Pd/La0.9Ba0.1AlO3−δ) has remarkably higher activity than other Pd catalysts at low temperatures (≤573 K) for NO reduction by propylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
(93 reference statements)
0
11
0
Order By: Relevance
“…The binding energies were calibrated with the C 1s peak at 284.8 eV. 24,[45][46][47] Before measurements, the Sr 1Àx Ba x ZrO 3 samples were reduced under H 2 atmosphere (N 2 /H 2 ¼ 1/3, total 240 SCCM) at 723 K for 2 h, which was the same procedure as the activity tests. These samples were transferred to the XPS apparatus without an air exposure using a transfer vessel.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
“…The binding energies were calibrated with the C 1s peak at 284.8 eV. 24,[45][46][47] Before measurements, the Sr 1Àx Ba x ZrO 3 samples were reduced under H 2 atmosphere (N 2 /H 2 ¼ 1/3, total 240 SCCM) at 723 K for 2 h, which was the same procedure as the activity tests. These samples were transferred to the XPS apparatus without an air exposure using a transfer vessel.…”
Section: Characterization Of the Catalystsmentioning
confidence: 99%
“…3,4,8,9 In addition, TWCs require high temperatures to achieve high purification performance. 10,11 We found from an earlier study that various catalytic reactions can proceed even at low temperatures when a DC electric field is applied to a semiconductor support. [12][13][14][15][16] Since then, we have attempted to apply this finding to TWCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the EHC method and plasmacatalyzed reaction require higher electric power consumption [3,4,8,9]. In addition, TWCs require high temperatures to achieve high purification performance [10,11]. We found from an earlier study that various catalytic reactions can proceed even at low temperatures when a DC electric field is applied to a semiconductor support [12][13][14][15][16].…”
mentioning
confidence: 99%
“…Subsequently, NOx is reduced by CxHyOz to N2 via R-NCO species. Higo et al also reported that the partially oxidized species of hydrocarbons (CxHyOz) are an extremely important intermediate species for HC-SCR over Pd/perovskite catalyst [11]. The catalyst shows high NOx reduction activity by virtue of the partially oxidized CxHy which is produced by highmobility lattice oxygen in the catalyst-support material.…”
mentioning
confidence: 99%